Manajemen Pajak pada Perusahaan Manufaktur di Bursa Efek Indonesia - Alfan Anggara Saputra; Yulius Kurnia Susanto (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to examine the factors that influence tax management in manufacturing companies on the Indonesia Stock Exchange. These factors are size, leverage, profitability, fixed asset intensity, inventory intensity, independent commissioner of tax management with effective tax rate indicators. Data from this study consisted of financial ratios based on financial statements from 69 manufacturing companies listed on the Indonesian stock exchange in the 2016-2018 period. This study states the results that profitability has a significant influence on tax management. This shows that if the higher the profit earned, it will make tax management more effective because the income earned is not part of the tax object. Other results state that company size, leverage, fixed asset intensity, inventory intensity, independent commissioners have no influence on tax management.